Improved removal of Cr(VI) by starch functionalized iron oxide nanoparticles - Singh P.N.; Tiwary D.; Sinha I. (My University, 2025)
We investigate the effect of starch functionalization of iron oxide nanoparticles on their adsorption of Cr(VI) from aqueous solutions. Iron oxide nanoparticles (IONPs) are synthesized by alkaline hydrolysis of FeCl3. The rate of addition of the base determines the time of aging of the reaction mixture at increasing pH values. This affects the iron oxide phase composition, nanoparticle sizes and their distribution. The purpose of this study is to first understand the effect of phase composition of such IONPs on their adsorption of Cr(VI) from aqueous solutions. Then to further investigate the effect of starch functionalization of these IONPs on their Cr(VI) adsorption capacity from aqueous medium. The results show that adsorption capacity changes with the phase composition. Further, for a given phase composition, starch functionalized iron oxide nanoparticles (SIONPs) exhibit significant improvement in adsorption capacities for Cr(VI) as compared to IONPs. Adsorption capacity is dependent on the pH value and at a given Cr(VI) concentration the adsorption capacity is found to be highest at pH 2 for all SIONPs and IONPs samples. The variation of adsorption capacity with pH depends on the nanoparticle phase composition as well as its starch functionalization. The removal of Cr(VI) by all SIONPs and IONPs follow Langmuir adsorption isotherm. The highest monolayer saturation adsorption capacity as obtained from the Langmuir adsorption isotherm for SIONPs is 9.02 mg/g. © 2014 Elsevier Ltd. All rights reserved.